Design and Construction of a Website-Based Posyandu Service System in Sukaraja Village - Putri Saniyyah; Ariansyah; Phinton Panglipur (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Posyandu services at the auxiliary health center are a place to carry out health service activities. The auxiliary health center (pustu) still carries out posyandu service activities for the community. Posyandu services are located in Sukaraja Village, South Prabumulih. Currently, health services in Sukaraja Village are still providing services manually and do not have a website. The purpose of this study is to build a website so that officers and the community can more easily record identity data. Based on the results of the study, the researcher tried to build a web-based service system using a qualitative descriptive method by collecting data in the form of observations, interviews, literature studies and developed using the Rapid Application Development (RAD) method. System design tools use Use Case, Activity Diagram and Class Diagram.